A production process for maintaining the physical properties of copper foil stable by on-line detection of roughness
Patent Information
- Application Number
- CN202611038243.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种通过在线检测粗糙度保持铜箔物性稳定的生产工艺,解决了现有电解加药系统因未考虑流体传输滞后而导致控制超调进而造成铜箔物性不稳定的问题
1、本发明通过配置包含季铵化聚乙烯基咪唑-环氧氯丙烷交联共聚物的混合添加剂,利用该共聚物分子链中的季铵阳离子向阴极表面高电流密度区迁移的特性,在微观凸起处形成物理空间位阻与静电排斥双重效应;这种控制机制有效阻碍了趋向凸起处的铜离子发生异常放电沉积,引导其向低电流密度的凹陷区域均匀还原,从而提升铜箔表面结晶的致密性与粗糙度的一致性。
Smart Images

Figure CN122898934A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrolytic copper foil preparation technology, specifically a production process that maintains the stability of copper foil properties by online roughness detection. Background Technology
[0002] Electrolytic copper foil is a core material for electronic components such as printed circuit boards and lithium-ion batteries. In the continuous electrolytic production process, the surface morphology and physical properties of the copper foil directly determine the quality of the final product, while the degree of crystallization density and surface roughness during the cathode electrodeposition process are highly dependent on the concentration balance of additives in the electrolyte. In order to control the cathode deposition state, sulfur-containing compounds, polyether compounds, and polymeric leveling agents are usually compounded in the base electrolyte.
[0003] In traditional continuous production lines for electrolytic copper foil, additive replenishment largely relies on manual experience or simple feedback loops for adjustment. With the introduction of automated control technology, some production lines have begun to adopt automatic dosing systems that combine online roughness detection with conventional PID control logic to achieve dynamic adjustment. However, the electrolytic reaction system itself has significant nonlinearity and large hysteresis characteristics. When the instrument detects that the surface roughness of the copper foil deviates from the set range and triggers a dosing command, the additive enters the electrolytic system from the injection point. After fluid mixing, transport, and diffusion, it reaches the cathode roller surface to participate in electrochemical competitive adsorption. This complete physical mass transfer and chemical reaction process has an inherent pure hysteresis time.
[0004] Most existing control logics rely on real-time errors for feedback, failing to incorporate the time delays in fluid transport and chemical reactions into their calculations. When a dosing command is executed, due to the hysteresis effect, the system cannot detect a significant improvement in roughness data in a short period. The feedback loop may misjudge this as insufficient adjustment, leading to the continuous generation and issuance of new dosing commands. This high-frequency error compensation will manifest itself after the hysteresis period ends, causing a sharp change in the local additive concentration at the reaction interface, resulting in severe overshoot and oscillations in the control system. This drastic fluctuation in concentration gradient not only disrupts the thermodynamic balance of the cathode interface but also ultimately leads to poor roughness consistency in continuously produced copper foils and causes physical instability issues such as runaway stress within the lattice. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a production process that maintains stable copper foil properties through online roughness detection, solving the problem of unstable copper foil properties caused by control overshoot due to the lack of consideration for fluid transport lag in existing electrolytic dosing systems.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A production process for maintaining stable copper foil properties through online roughness detection includes the following steps: S1, prepare the basic electrolyte, and combine sulfur-containing compounds, polyether compounds and quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymers into a mixed additive mother liquor; inject the mixed additive mother liquor into the electrolytic cell through a metering pump, so as to control the cathode deposition potential by utilizing the dual mechanism of steric hindrance and charge repulsion of the crosslinked copolymer. S2, a detection point is set between the electrolytic cell outlet and the winding machine to collect the roughness data of the copper foil surface in real time; S3, the data acquisition and processing module extracts the values in the data window according to the set period, removes abnormal extreme values based on the 3σ criterion, calculates the arithmetic mean of the remaining effective values, and compares it with the preset target roughness range. S4. When the arithmetic mean deviates from the target range, the data acquisition and processing module sends a flow adjustment command to the metering pump. After the command is executed, the system is forced to enter a period of adjustment lockout. During the lockout period, only data is collected and any new flow adjustment command is blocked to compensate for the pure lag time of the additive fluid being transferred to the cathode roller surface. S5. After the lockout period ends, the system calculates the slope of the change in the average roughness value. If the average value still exceeds the limit, based on the comparison between the absolute value of the change slope and the preset slope threshold, the system chooses to multiply the subsequent adjustment amount by the weight coefficient for derated adjustment or to perform full step adjustment, and re-enters the adjustment lockout period. If the average value returns to the target range, the current flow rate remains unchanged.
[0007] By adopting the above technical solution, and using a specific compounded additive combined with closed-loop control logic possessing hysteresis compensation and trend prediction mechanisms, system oscillations can be effectively suppressed, achieving precise control of the cathode deposition state and maintaining long-term stability of copper foil roughness. The specific reaction mechanism and control principle are reflected in the following aspects: During the competitive adsorption and discharge deposition process at the electrode interface, the basic reaction on the cathode roller surface is the reduction deposition of copper ions by acquiring electrons. After the mixed additives enter the electrolyte, sulfur-containing compounds act as accelerating components, polyether compounds act as inhibiting components, and quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymers act as leveling and modifying components, all of which compete for adsorption at the cathode interface. Specifically, the crosslinked copolymer molecular chains contain quaternary ammonium cation structures and imidazole ring groups. Under the drive of the cathode electric field, the positively charged quaternary ammonium cations preferentially migrate and attach to the high current density regions of the microscopic protrusions on the surface. On the one hand, the relatively complex polymer chain segments constitute physical steric hindrance; on the other hand, the positively charged groups electrostatically repel the hydrated copper ions in the solution that tend to move to this location. The above mechanism hinders the reduction discharge of copper ions at the protrusions and promotes the deposition of copper ions in the low current density recessed regions, achieving smooth crystallization.
[0008] To obtain accurate surface deposition morphology, the system needs to perform data denoising and hysteresis locking. In actual production, the 3σ criterion is used to remove local high-frequency noise data caused by winding vibration or surface moisture, and the arithmetic mean reflecting the true deposition morphology is extracted. It should be noted that in industrial fluid systems, there is a time lag between the injection of additives from the metering pump and their diffusion to the cathode roller interface to take effect. Therefore, after the flow regulation command is executed, a regulation lockout period is initiated to forcibly cut off the immediate command issuance of the feedback loop. This mechanism allows the control system to remain in an observation state during the fluid mass transfer blank period, preventing the closed loop from erroneously sending dosing commands due to the failure to detect changes in surface roughness.
[0009] Building upon the hysteresis locking mechanism, the system further incorporates dynamic prediction and derating correction logic. The slope of the average roughness value is extracted as a parameter to determine the system's response rate. When the roughness is still outside the target range but the absolute value of the slope is large, it indicates that the reagent concentration from the previous flow rate adjustment has reached the cathode surface and the chemical leveling reaction is accelerating. In this case, the system performs derating adjustment, limiting the new dosing step size to eliminate the risk of increased cathode polarization due to over-addition. Conversely, when the absolute value of the slope is small, full-step adjustment is performed to quickly break the current low-concentration equilibrium at the electrolyte interface, rapidly returning the overall deposition state to the target range.
[0010] Preferably, in step S1, the specific parameters for configuring the basic electrolyte are as follows: the basic electrolyte contains 70-100 g / L of copper ions, 90-130 g / L of sulfuric acid, and 20-45 mg / L of chloride ions; at the same time, a heat exchange circulation loop is configured to control the electrolyte temperature to be stable at 45-60℃.
[0011] By adopting the above technical solution, the limited ion concentration maintains the high conductivity and ion diffusion flux of the basic electrolyte; combined with the constant system temperature of the heat exchange circulation loop, the thermodynamic equilibrium of the adsorption and desorption rates of the mixed additives at the cathode interface can be maintained, ensuring the consistency of the overall electrodeposition morphology.
[0012] Preferably, in step S1, the mixed additive mother liquor needs to be continuously injected through a metering pump to maintain the concentration of sulfur-containing compounds in the electrolytic cell solution at 1.0-5.0 mg / L, the concentration of polyether compounds at 5.0-20.0 mg / L, and the concentration of quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer at 0.5-3.0 mg / L; wherein, the sulfur-containing compounds are specifically selected from sodium polydisulfide dipropanesulfonate or sodium 3-mercapto-1-propanesulfonate, and the polyether compounds are specifically polyethylene glycol.
[0013] By adopting the above technical solution and setting a specific concentration ratio gradient, the complexation inhibition film formed by polyethylene glycol and chloride ions and the depolarization effect of sulfur-containing compounds are balanced. On this basis, a polarization potential window is reserved for the cross-linked copolymer to carry out local leveling reaction, so as to avoid the increase of copper foil lattice stress caused by excessive concentration of a single type of additive.
[0014] Preferably, in step S1, before starting the automatic closed-loop control system, the production line initialization settings need to be performed: the conveyor speed of the copper foil production line is set to be constant at 6m / min, and the initial liquid flow rate of the metering pump is set to 3.0-8.0L / min based on the volume of the electrolytic cell and the state of the base liquid.
[0015] By adopting the above technical solution and matching a constant conveyor speed with an initial liquid flow rate in a specific range, the basic cathode polarization potential can be quickly established in the early stage of electrolysis system operation, thereby shortening the process time required to enter the closed-loop regulation state.
[0016] Preferably, in step S2, the hardware setup and operation mode for real-time acquisition are as follows: In the constant speed belt travel area between the electrolytic cell outlet and the winding machine, 13 detection points are uniformly set along the width direction of the copper foil using a non-contact laser roughness meter; and the signals of each detection point are synchronously acquired at a sampling frequency of 1Hz-5Hz to form a real-time roughness dataset covering the entire width of the copper foil.
[0017] By adopting the above technical solution, non-contact laser measurement does not cause physical scratches on the copper foil surface. At the same time, the use of multi-point transverse array arrangement combined with high-frequency continuous sampling can fully collect physical morphology information of the entire area and vertical depth, reducing systematic errors caused by single-point measurement.
[0018] Preferably, in step S3, the specific data processing mechanism for data filtering and analysis is as follows: the data acquisition and processing module extracts the dataset collected within each 10-second time window as a data extraction window; after removing outliers that deviate from the arithmetic mean by more than 3 times the standard deviation, the arithmetic mean of the valid data within the data window is recalculated; and the result is compared with the preset target roughness range of 0.3μm to 0.5μm for limit judgment.
[0019] By adopting the above technical solution, time window slicing processing combined with statistical algorithms can effectively filter out discrete values caused by environmental interference factors, restore the true distribution trend of the data sequence, and provide a high-confidence reference standard for subsequent traffic regulation.
[0020] Preferably, in step S4, the data acquisition and processing module generates corresponding flow increase or decrease adjustment commands based on the deviation direction. The specific flow adjustment ratio is set as follows: for every 0.1 μm that the arithmetic mean exceeds or falls below the target range, the data acquisition and processing module controls the flow rate of the metering pump to decrease or increase by 0.1-0.5 L / min.
[0021] By adopting the above technical solution, a fixed relationship between error and driving force is established, which effectively limits the amplitude boundary of single feedback adjustment and avoids the rapid reconstruction of the additive concentration gradient in the reaction tank caused by large-scale adjustment.
[0022] Preferably, in step S4, the duration of the adjustment lockout period that the system is forced to enter after the instruction is executed is set to 3 to 10 minutes. During the adjustment lockout period, the data acquisition and processing module continues to execute steps S2 and S3 to maintain continuous monitoring of the trend of copper foil roughness change, but actively intercepts and blocks any new flow adjustment instructions generated based on the latest arithmetic average until the countdown of the current lockout period ends.
[0023] By adopting the above technical solution, the lock-in period covers the minimum fluid diffusion time of the additive in the industrial electrolyzer from the injection end to the reaction interface; during the lock-in period, the monitoring function accumulates process data and simultaneously cuts off the input of the actuator, fundamentally avoiding the transformation of continuous over-limit judgments during the fluid delay stage into superimposed malfunctions.
[0024] Preferably, in step S5, the specific data extraction and comparison method for calculating the slope of change is as follows: at the end of the current adjustment lock period, the system extracts the roughness arithmetic mean within the latest 1-minute time window, and calculates the difference between it and the value recorded at the beginning of the adjustment lock period to obtain the slope of change representing the roughness recovery trend; the system presets the absolute value threshold of the slope to be 0.05-0.08μm / min.
[0025] By adopting the above technical solution, a differential trend quantity is constructed by using the difference between the average value of the end segment and the initial value, thereby quantifying the physical velocity of the influence of the previous control action on the interface response.
[0026] Preferably, in step S5, the specific rules for executing the adjustment logic based on trend prediction are as follows: if the absolute value of the change slope is greater than or equal to the preset slope threshold, the calculated theoretical adjustment amount is multiplied by a weighting coefficient of 0.3-0.7 for de-rating adjustment; if the absolute value of the change slope is less than the preset slope threshold, full-amount step adjustment is executed; after a single adjustment action is completed, the system immediately triggers a new round of adjustment lock-up period.
[0027] By adopting the above technical solution, the dynamic convergence of the adjustment step size is achieved by introducing the slope of state change as a compensation coefficient; the weight of human intervention is reduced when the system’s natural recovery kinetic energy is strong, while the driving force is maintained when the recovery kinetic energy is insufficient, thereby effectively suppressing the oscillation problem caused by a single control logic in the edge region.
[0028] This invention provides a production process for maintaining stable copper foil properties through online roughness detection. It offers the following advantages: 1. This invention utilizes a mixed additive containing a quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer. By taking advantage of the migration characteristics of quaternary ammonium cations in the copolymer molecular chain to the high current density region of the cathode surface, a dual effect of physical steric hindrance and electrostatic repulsion is formed at the micro-protrusions. This control mechanism effectively prevents the abnormal discharge and deposition of copper ions tending towards the protrusions, and guides them to be uniformly reduced to the low current density recessed region, thereby improving the density and roughness consistency of the copper foil surface crystal.
[0029] 2. This invention introduces a regulation lockout period mechanism into the flow regulation feedback loop, and, in conjunction with a data denoising algorithm based on the 3σ criterion, solves the pure time delay problem commonly found in industrial electrolyte fluid transmission. By forcing the system into a lockout state of monitoring only and not regulating after the dosing command is issued, sufficient buffer time is given for the mass transfer of the additive fluid and the chemical reaction at the cathode interface, avoiding the control system from repeatedly sending dosing commands due to failure to detect changes in surface morphology in time, and eliminating frequent malfunctions and overshoot oscillations in the closed loop.
[0030] 3. This invention constructs a trend prediction and dynamic step size correction logic based on the slope of the change in the average roughness value, enabling the system to autonomously adjust the control intensity according to the speed of natural convergence of the electrolytic state. When the interface leveling reaction is detected to be accelerating, the system reduces the intervention amplitude by multiplying by a weighting coefficient. When the recovery power is insufficient, the system maintains full step size drive. This dynamic compensation based on the state slope achieves smooth convergence of the dosing control, ensuring the long-term stability of the physical properties of copper foil in continuous production cycles. Attached Figure Description
[0031] Figure 1 This is a schematic diagram of the roughness variation curve over time under the step response of the present invention; Figure 2 This is a schematic diagram of the cathode deposition potential polarization curves under different leveling agent systems according to the present invention; Figure 3 This is a schematic diagram illustrating the statistical changes in copper foil roughness during 24 hours of continuous operation according to the present invention. Figure 4 This is a schematic diagram comparing the flow overshoot of a fixed displacement pump under different control logics according to the present invention; Figure 5This is a schematic diagram comparing the tensile strength of copper foil in continuous production batches according to the present invention; Figure 6 This is a schematic diagram comparing the elongation at break of copper foil in continuous production batches according to the present invention. Figure 7 This is a schematic diagram comparing the system roughness recovery time under sudden disturbances according to the present invention; Figure 8 This is a schematic diagram of the online roughness closed-loop control system of the present invention. Detailed Implementation
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Please see the appendix Figure 1 -Appendix Figure 8 : The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0034] Sodium polydisulfide dipropane sulfonate, CAS number 27206-35-5, is a commercially available powder reagent with a purity greater than 99%. Sodium 3-mercapto-1-propanesulfonate, CAS number 17636-10-1, is a commercially available powder reagent with a purity greater than 99%. Polyethylene glycol, CAS number 25322-68-3, is a linear homopolymer formed by ring-opening polymerization of ethylene oxide; the polyethylene glycol used in this invention has a weight-average molecular weight of 8000 and a molecular weight distribution index ranging from 1.05 to 1.15, and is a conventional commercially available product. 1-Vinylimidazole, CAS No. 1072-63-5, has a structure containing a polymerizable vinyl group and a coordinating imidazole ring. It is a commercially available reagent with a purity greater than 99%. Epichlorohydrin, CAS number 106-89-8, is a commercially available reagent with a purity greater than 99%. Azobisisobutyronitrile (AIBN), CAS number 78-67-1, is a commercially available reagent with a purity greater than 99%.
[0035] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.
[0036] Preparation Example 1: This preparation example provides a method for preparing quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A, including the following steps: Dissolve 100 parts of 1-vinylimidazole in 300 parts of anhydrous ethanol, purge with nitrogen to remove oxygen for 30 minutes, then add 1 part of azobisisobutyronitrile; under reflux and constant stirring conditions, heat to 72°C and react for 14 hours. After the reaction was completed, acetone was used for precipitation and washing, and the solid polyvinyl imidazole was obtained by drying in a vacuum drying oven at 50°C. 100 parts of the above polyvinyl imidazole solid were dissolved in 800 parts of deionized water, the temperature was raised to 82°C, and 30 parts of epichlorohydrin were slowly added dropwise. After the addition was completed, the mixture was stirred at a constant temperature for 20 hours. After the system cooled to room temperature, it was dialyzed in deionized water for 48 hours using a dialysis bag with a molecular weight cutoff of 3000 Da to obtain a pure aqueous solution of quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A.
[0037] Preparation Example 2: This preparation example provides a method for preparing quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer B, including the following steps: Dissolve 100 parts of 1-vinylimidazolium in 400 parts of anhydrous ethanol, purge with nitrogen to remove oxygen for 30 minutes, then add 0.5 parts of azobisisobutyronitrile; under reflux and constant stirring conditions, heat to 70°C and react for 12 hours. After the reaction was completed, acetone was used for precipitation and washing, and the solid polyvinyl imidazole was obtained by drying in a vacuum drying oven at 50°C. 100 parts of the above polyvinyl imidazole solid were dissolved in 900 parts of deionized water, the temperature was raised to 80°C, and 20 parts of epichlorohydrin were slowly added dropwise. After the addition was completed, the mixture was stirred at a constant temperature for 18 hours. After the system cooled to room temperature, it was dialyzed in deionized water for 72 hours using a dialysis bag with a molecular weight cutoff of 3000 Da to obtain a pure aqueous solution of quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer B.
[0038] Preparation Example 3: This preparation example provides a method for preparing quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer C, including the following steps: Dissolve 100 parts of 1-vinylimidazole in 200 parts of anhydrous ethanol, purge with nitrogen to remove oxygen for 30 minutes, then add 1.5 parts of azobisisobutyronitrile; under reflux and constant stirring conditions, heat to 75°C and react for 16 hours. After the reaction was completed, acetone was used for precipitation and washing, and the solid polyvinyl imidazole was obtained by drying in a vacuum drying oven at 50°C. 100 parts of the above polyvinyl imidazole solid were dissolved in 700 parts of deionized water, the temperature was raised to 85°C, and 45 parts of epichlorohydrin were slowly added dropwise. After the addition was completed, the mixture was stirred at a constant temperature for 24 hours. After the system cooled to room temperature, it was dialyzed in deionized water for 60 hours using a dialysis bag with a molecular weight cutoff of 3000 Da to obtain a pure aqueous solution of quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer C.
[0039] Example 1: This embodiment provides a production process for maintaining the stability of copper foil properties by online roughness detection, including the following steps: S1, prepare a basic electrolyte containing 85 g / L copper ions, 110 g / L sulfuric acid, and 30 mg / L chloride ions, and control the electrolyte temperature at 50°C; combine sodium polydisulfide dipropane sulfonate, polyethylene glycol, and the quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A obtained in Preparation Example 1 as a mixed additive mother liquor; inject the mixed additive mother liquor into the electrolytic cell using a metering pump to maintain a stable concentration of sodium polydisulfide dipropane sulfonate at 3.0 mg / L, a stable concentration of polyethylene glycol at 12.0 mg / L, and a stable concentration of quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A at 1.5 mg / L; set the copper foil production line speed to 6 m / min and the initial flow rate of the metering pump to 5.0 L / min.
[0040] S2. Between the electrolytic cell outlet and the winding machine, 13 detection points are set along the width direction of the copper foil using a non-contact laser roughness meter to collect the roughness data of the copper foil surface in real time at a sampling frequency of 3Hz.
[0041] S3. The data acquisition and processing module extracts the values in the data window every 10 seconds. After removing outliers based on the 3σ criterion, it calculates the arithmetic mean of the remaining valid values and compares it with the preset target roughness range of 0.3μm to 0.5μm.
[0042] S4. When the above arithmetic mean deviates from the target range, the data acquisition and processing module sends an adjustment command to the metering pump. For every 0.1 μm that the roughness exceeds or falls below the target range, the metering pump flow rate decreases or increases by 0.3 L / min. After the command is executed, the system is forced to enter a 5-minute adjustment lockout period. During the lockout period, only data is collected, and any new flow adjustment commands are blocked.
[0043] S5. After the lockout period ends, the system extracts the latest 1-minute roughness average value and calculates the change slope with the initial value at the beginning of the lockout. If the average value still exceeds the limit, but the absolute value of the change slope is greater than or equal to 0.05 μm / min, the calculated subsequent adjustment amount is multiplied by a weighting coefficient of 0.5 for halved adjustment, and the system re-enters the 5-minute adjustment lockout period. If the average value still exceeds the limit and the absolute value of the change slope is less than 0.05 μm / min, the system performs full step adjustment and re-enters the adjustment lockout period. If the average value returns to the target range, the current flow rate is maintained. The above steps are repeated to form a continuous closed-loop monitoring system.
[0044] Example 2: This embodiment provides a production process for maintaining the stability of copper foil properties by online roughness detection, including the following steps: S1. Prepare a basic electrolyte containing 70 g / L copper ions, 90 g / L sulfuric acid, and 20 mg / L chloride ions, and control the electrolyte temperature at 45°C. Prepare a mixed additive mother liquor by compounding sodium 3-mercapto-1-propanesulfonate, polyethylene glycol, and the quaternized polyvinylimidazolium-epoxychloropropane crosslinked copolymer B obtained in Preparation Example 2. Inject the mixed additive mother liquor into the electrolytic cell using a metering pump to maintain a stable concentration of sodium 3-mercapto-1-propanesulfonate at 1.0 mg / L, polyethylene glycol at 5.0 mg / L, and quaternized polyvinylimidazolium-epoxychloropropane crosslinked copolymer B at 0.5 mg / L. Set the copper foil production line speed to 6 m / min and the initial flow rate of the metering pump to 3.0 L / min.
[0045] S2. Between the electrolytic cell outlet and the winding machine, 13 detection points are set along the width direction of the copper foil using a non-contact laser roughness meter to collect the roughness data of the copper foil surface in real time at a sampling frequency of 1Hz.
[0046] S3. The data acquisition and processing module extracts the values in the data window every 10 seconds. After removing outliers based on the 3σ criterion, it calculates the arithmetic mean of the remaining valid values and compares it with the preset target roughness range of 0.3μm to 0.5μm.
[0047] S4. When the above arithmetic mean deviates from the target range, the data acquisition and processing module sends an adjustment command to the metering pump. For every 0.1 μm that the roughness exceeds or falls below the target range, the metering pump flow rate decreases or increases by 0.1 L / min. After the command is executed, the system is forced to enter a 3-minute adjustment lockout period. During the lockout period, only data is collected, and any new flow adjustment commands are blocked.
[0048] S5. After the lockout period ends, the system extracts the latest 1-minute roughness average value and calculates the change slope with the initial value at the beginning of the lockout. If the average value still exceeds the limit, but the absolute value of the change slope is greater than or equal to 0.05 μm / min, the calculated subsequent adjustment amount is multiplied by a weighting coefficient of 0.3 for derating adjustment, and the system re-enters the 3-minute adjustment lockout period. If the average value still exceeds the limit and the absolute value of the change slope is less than 0.05 μm / min, the system performs full-step adjustment and re-enters the adjustment lockout period. If the average value returns to the target range, the current flow rate is maintained. The above steps are repeated to form a continuous closed-loop monitoring system.
[0049] Example 3: This embodiment provides a production process for maintaining the stability of copper foil properties by online roughness detection, including the following steps: S1. Prepare a basic electrolyte containing 100 g / L copper ions, 130 g / L sulfuric acid, and 45 mg / L chloride ions, and control the electrolyte temperature at 60°C. Prepare a mixed additive mother liquor by compounding sodium dithiodipropane sulfonate, polyethylene glycol, and the quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer C obtained in Preparation Example 3. Inject the mixed additive mother liquor into the electrolytic cell using a metering pump to maintain a stable concentration of sodium dithiodipropane sulfonate at 5.0 mg / L, polyethylene glycol at 20.0 mg / L, and quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer C at 3.0 mg / L. Set the copper foil production line speed to 6 m / min and the initial flow rate of the metering pump to 8.0 L / min.
[0050] S2. Between the electrolytic cell outlet and the winding machine, 13 detection points are set along the width direction of the copper foil using a non-contact laser roughness meter to collect the roughness data of the copper foil surface in real time at a sampling frequency of 5Hz.
[0051] S3. The data acquisition and processing module extracts the values in the data window every 10 seconds. After removing outliers based on the 3σ criterion, it calculates the arithmetic mean of the remaining valid values and compares it with the preset target roughness range of 0.3μm to 0.5μm.
[0052] S4. When the above arithmetic mean deviates from the target range, the data acquisition and processing module sends an adjustment command to the metering pump. For every 0.1 μm that the roughness exceeds or falls below the target range, the metering pump flow rate decreases or increases by 0.5 L / min. After the command is executed, the system is forced to enter a 10-minute adjustment lockout period. During the lockout period, only data is collected, and any new flow adjustment commands are blocked.
[0053] S5. After the lockout period ends, the system extracts the latest 1-minute roughness average value and calculates the change slope with the initial value at the beginning of the lockout. If the average value still exceeds the limit, but the absolute value of the change slope is greater than or equal to 0.05 μm / min, the calculated subsequent adjustment amount is multiplied by a weighting coefficient of 0.7 for derating adjustment, and the system re-enters the 10-minute adjustment lockout period. If the average value still exceeds the limit and the absolute value of the change slope is less than 0.05 μm / min, the system performs full-step adjustment and re-enters the adjustment lockout period. If the average value returns to the target range, the current flow rate is maintained. The above steps are repeated to form a continuous closed-loop monitoring system.
[0054] Example 4: This embodiment provides a production process for maintaining the stability of copper foil properties by online roughness detection, including the following steps: S1. Prepare a basic electrolyte containing 90 g / L copper ions, 120 g / L sulfuric acid, and 35 mg / L chloride ions, and control the electrolyte temperature at 55°C. Prepare a mixed additive mother liquor by compounding sodium dithiodipropane sulfonate, polyethylene glycol, and the quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A obtained in Preparation Example 1. Inject the mixed additive mother liquor into the electrolytic cell using a metering pump to maintain a stable concentration of sodium dithiodipropane sulfonate at 4.0 mg / L, polyethylene glycol at 15.0 mg / L, and quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A at 2.0 mg / L. Set the copper foil production line speed to 6 m / min and the initial flow rate of the metering pump to 6.0 L / min.
[0055] S2. Between the electrolytic cell outlet and the winding machine, 13 detection points are set along the width direction of the copper foil using a non-contact laser roughness meter to collect the roughness data of the copper foil surface in real time at a sampling frequency of 4Hz.
[0056] S3. The data acquisition and processing module extracts the values in the data window every 10 seconds. After removing outliers based on the 3σ criterion, it calculates the arithmetic mean of the remaining valid values and compares it with the preset target roughness range of 0.3μm to 0.5μm.
[0057] S4. When the above arithmetic mean deviates from the target range, the data acquisition and processing module sends an adjustment command to the metering pump. For every 0.1 μm that the roughness exceeds or falls below the target range, the metering pump flow rate decreases or increases by 0.4 L / min. After the command is executed, the system is forced to enter an 8-minute adjustment lockout period. During the lockout period, only data is collected, and any new flow adjustment commands are blocked.
[0058] S5. After the lockout period ends, the system extracts the latest 1-minute roughness average value and calculates the change slope with the initial value at the beginning of the lockout. If the average value still exceeds the limit, but the absolute value of the change slope is greater than or equal to 0.08 μm / min, the calculated subsequent adjustment amount is multiplied by a weighting coefficient of 0.4 for derating adjustment, and the system re-enters the 8-minute adjustment lockout period. If the average value still exceeds the limit and the absolute value of the change slope is less than 0.08 μm / min, the system performs full-step adjustment and re-enters the adjustment lockout period. If the average value returns to the target range, the current flow rate is maintained. The above steps are repeated to form a continuous closed-loop monitoring system.
[0059] Comparative Example 1: Compared with Example 1, the difference is that: a non-contact laser roughness tester and data acquisition and processing module are not used for online closed-loop control; online detection and automatic adjustment are replaced with the traditional offline manual sampling detection mode, that is, copper foil samples are cut at the winding point every 2 hours for roughness testing, and the operator manually adjusts the flow rate of the metering pump according to the offline test results. All other aspects are the same.
[0060] Comparative Example 2: Compared with Example 1, the difference is that in the rate adjustment steps of S4 and S5, the adjustment lock-in period and trend prediction logic are removed; that is, when the roughness arithmetic mean is detected to deviate from the target range, the data acquisition and processing module continuously sends adjustment instructions in real time at a fixed step size and executes them immediately without any forced lock-in waiting, and the rest are the same.
[0061] Comparative Example 3: Compared with Example 1, the difference is that in the closed-loop control step of S5, the trend compensation logic of slope calculation and halving adjustment is eliminated; that is, after the 5-minute adjustment lock-in period ends, as long as the average roughness value still exceeds the limit, the system will rigidly execute the full step flow adjustment regardless of its trend, and the rest are the same.
[0062] Comparative Example 4: Compared with Example 1, the difference is that in the additive preparation step of S1, the leveling agent quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer A in the mixed additive mother liquor is replaced with a conventional commercially available leveling agent gelatin of equal mass concentration, and the rest are the same.
[0063] Test Example 1: The production system described in Example 1, which includes a metering pump, an electrolytic cell, and a non-contact laser roughness meter, is started and run to an initial stable state. At this time, the basic electrolyte and the mixed additives are circulated according to the ratio in Example 1. The system maintains an initial pump flow rate of 5.0 L / min, and the roughness of the copper foil surface is stabilized at about 0.40 μm.
[0064] At the 60th second, the control mode of the metering pump is switched from automatic closed-loop to manual mode from the control system background, all automatic adjustment commands are disabled, and a fixed-amplitude flow step control command is manually input to the metering pump, so that its operating flow rate is instantly increased from 5.0L / min to 7.0L / min, and then the flow rate is kept constant.
[0065] Starting from 0 seconds, the data acquisition and processing module continuously extracts and records the system's timestamp, the real-time flow feedback value of the metering pump, and the arithmetic mean roughness Ra value output by the laser roughness meter every 10 seconds, with the total recording time set to 600 seconds.
[0066] After the experiment, the recorded dataset was exported, and the moment when the pump flow rate jumped and the moment when the roughness Ra value first exceeded the trend change of the instrument fluctuation error were observed and extracted. The difference between the two is the inherent pure lag time of the current electrolytic cell fluid and physical system.
[0067] Table 1: Test data of pure time delay and roughness change of the system under step response.
[0068] According to Table 1 and Figure 1 When the system experiences a sudden increase in the flow rate of the metering pump at the 60th second, the microstructure of the copper foil surface does not immediately follow suit. Observation of the test interval shows that the roughness Ra value does not show a substantial decreasing trend until around the 240th second. This indicates that there is a pure lag time of about 180 seconds in the fluid transfer of the industrial-grade electrolytic cell, that is, the additive needs a fixed physical mass transfer time to form a stable adsorption layer on the cathode surface. If the control algorithm ignores this lag effect, the module will continuously issue adjustment commands because the sensor readings do not change significantly in the early stage, eventually leading to system oscillation. Example 1 sets an adjustment lock-in period in the control logic that matches this lag time, cuts off the misjudgment closed loop caused by the physical mass transfer delay, provides the necessary time margin for fluid mixing and electrochemical polarization to establish a new equilibrium, and verifies the scientific nature of the anti-oscillation compensation mechanism of this scheme.
[0069] Test Example 2: A standard three-electrode electrochemical test cell was assembled using 99.99% pure copper foil as the working electrode with an area of 1cm×1cm, a large-area platinum sheet as the counter electrode, and a saturated silver chloride electrode as the reference electrode.
[0070] Three sets of electrolyte systems were prepared for parallel comparison as experimental subjects. The first set was the basic blank solution, containing only 85 g / L copper ions, 110 g / L sulfuric acid, 30 mg / L chloride ions, and basic concentrations of SPS (3.0 mg / L) and PEG (12.0 mg / L); the second set was the electrolyte corresponding to Comparative Example 4, which was the basic blank solution with 1.5 mg / L of conventional gelatin added; the third set was the electrolyte corresponding to Example 1, which was the basic blank solution with 1.5 mg / L of quaternized polyvinylimidazolium-epoxychloropropane crosslinked copolymer A added.
[0071] The electrolyte was kept in a constant temperature water bath at 50°C. The three solutions were placed in the electrochemical workstation and left to stand for 5 minutes to ensure that the electrode surface reached equilibrium.
[0072] The test mode was set to linear voltammetry scan, with the scan range from open circuit potential towards cathode to -0.8V, and the scan rate set to 5mV / s. The current density was extracted and recorded in the background at 2A / dm³. 2 Up to 10A / dm 2 The specific values of the cathode deposition potential corresponding to multiple representative working nodes within the interval.
[0073] Table 2: Test data of cathodic deposition potential under different leveling agent systems
[0074] According to Table 2 and Figure 2 The electrochemical polarization behavior of cathode deposition varied significantly under different leveling agent systems; the basic test group without leveling agent maintained the most positive cathode potential at all current densities; in Comparative Example 4, the polarization increased after the introduction of traditional gelatin, but its steric hindrance effect was consumed quickly at high current densities; in contrast, the QPVI-E polymer used in Example 1 exhibited excellent electrochemical adsorption characteristics; at 6 A / dm 2 Under the operating current, the deposition potential shifted significantly negatively to -0.375V; this indicates that the quaternary ammonium cations of the polymer can work synergistically with chloride ions to form a dense suppression film at the microscopic protrusions of the cathode interface, blocking the tip discharge effect and forcing the current to shift to the depressions; the dual mechanism of steric hindrance and charge repulsion brought about by this structure suppresses the abnormal coarsening of individual copper grains, promotes high-frequency renucleation, and improves the uniformity of the macroscopic morphology of the copper foil.
[0075] Test Example 3: The electrolysis systems and production control models corresponding to Examples 1 to 4 and Comparative Examples 1 to 4 were selected as test objects; the line speed of each production line was uniformly set to 6 m / min, and the target roughness range was set to 0.3 μm to 0.5 μm. The system was then started to enter the continuous electrolytic foil making process.
[0076] Maintain continuous operation of each production line for 24 hours. During operation, keep hardware parameters such as basic electrolyte temperature and current density constant, without any additional manual intervention, and allow the fluid control to be automatically taken over by the program logic set by each group.
[0077] After the operation is completed, the complete online roughness record logs for each group within 24 hours are exported from the background data acquisition and processing module; for the manual inspection mode of Comparative Example 1, the raw data of 12 offline sampling tests throughout the day are collected.
[0078] Perform full numerical statistics on the exported datasets, calculate the arithmetic mean, maximum and minimum values of the data sets of each running group, and deduce the roughness range and the standard deviation reflecting the overall data dispersion.
[0079] Table 3: Statistical data of roughness Ra for each group after 24 hours of continuous operation
[0080] According to Table 3 and Figure 3 Different control mechanisms exhibit significant differences in their ability to maintain long-term stable control of macroscopic morphology. Comparative Example 2, due to its use of high-frequency online feedback but lack of a regulation lock-in period, misjudged fluid mass transfer delay as insufficient regulation and continuously superimposed commands, resulting in repeated fluctuations in the leveling agent concentration and systematic oscillations in product roughness, with a range as high as 0.556 μm. Comparative Example 1 employed manual offline sampling, and the detection time difference led to long-term drift. Examples 1 to 4, by embedding forced dead zones and half-step slope compensation in the underlying algorithm, maintained all discrete indicators at extremely low levels. Taking Example 1 as an example, the standard deviation was controlled at 0.021, and the roughness was always maintained within the process window. The dead zone mechanism reserved a physical mass transfer window for fluid diffusion, and the introduction of the changing slope endowed the system with feedforward compensation capability for concentration changes. The two combined filtered out disturbances at the microscopic crystallization level, ensuring the stability of long-term continuous operation.
[0081] Test Example 4: The control programs corresponding to Examples 1 to 4, Comparative Examples 2 (excluding the adjustment lock-in period) and 3 (excluding the trend compensation logic) were loaded into the PLC main control module of the independent electrolysis system. The initial reference flow rate of each group was uniformly calibrated to 5.0 L / min, and the roughness target window was set to 0.3 μm to 0.5 μm, so that the system could be started and enter continuous operation under standard parameters.
[0082] At the 30th minute of system operation, an equivalent simulated disturbance operation was applied to the mixed additive mother liquor pipeline of all test groups, that is, the opening of the pipeline back pressure valve was artificially reduced to induce insufficient drug supply in a short period of time. Subsequently, each system relied entirely on its own closed-loop control algorithm to perform autonomous correction.
[0083] Maintain continuous operation of each production line for 24 hours; during operation, no manual parameter corrections are made, and the control log module in the system background records the timestamp and specific adjustment of every speed / flow rate modification command issued to the quantitative pump.
[0084] After the operation cycle ends, extract and summarize the data in the control log, and count the total number of times each group of systems issues speed adjustment actions to the fixed displacement pump within 24 hours; extract the absolute difference between the actual pump flow rate and the 5.0 L / min reference value after a single adjustment, and record the maximum flow overshoot and the arithmetic mean overshoot during the operation cycle.
[0085] Table 4: Statistical Data of Fixed Displacement Pump Operation Status under Various Control Logics
[0086] According to Table 4 and Figure 4 The way the control algorithm handles trend changes directly affects the stability of the fluid delivery end of the system. Comparative Example 3 lacks trend prediction and halving adjustment logic, and still uses a fixed full step size after the dead zone ends, failing to digest the accumulated drug concentration gradient within the system. This fixed full step size adjustment causes a lag in the mixing of newly added drug with the previously incompletely mixed drug in the tank, resulting in a sudden thickening of the inhibition film and triggering a reverse roughness exceedance, ultimately forming an oscillating overshoot with a maximum 24-hour overshoot of 2.13 L / min. Example groups achieved smooth convergence by extracting the slope of change and introducing a feedforward compensation mechanism. Taking Example 1 as an example, when the system detects a convergence trend in roughness, it performs approximate fine-tuning using halving weights to avoid a surge in local leveling agent concentration. Example 1 limits the maximum daily overshoot to within 0.82 L / min, eliminating frequent and drastic mechanical control actions and ensuring the consistency of the electrolyte's chemical state from the source.
[0087] Test Example 5: The electrolytic foil-making systems corresponding to Example 1, Comparative Example 1 which relied on manual offline adjustment, and Comparative Example 4 which used conventional gelatin leveling agent were used as test objects. The target roughness range was uniformly set to 0.3 μm to 0.5 μm, and the three production lines were put into continuous operation at a line speed of 6 m / min.
[0088] During the 24-hour cycle of continuous and stable system operation, a complete copper foil sample is cut at the winding end every 2 hours. The obtained sample is cut into rectangular strips of 150mm×15mm according to the IPC-TM-650 industry standard, and 12 test strips at different production time points are collected for each group.
[0089] Tensile tests were performed on all collected rectangular specimens using a universal tensile testing machine. The ambient temperature was kept constant at 25°C, and the separation speed of the tension clamps was set to 50 mm / min. Unidirectional constant speed tension was maintained until the specimens completely broke.
[0090] The maximum load value at the moment of fracture and the absolute elongation of the gauge length before fracture of each sample are read and recorded from the equipment backend output. Based on this, the room temperature tensile strength and elongation at break of each batch of samples are calculated. After removing invalid data, the physical property parameters of each time period are summarized.
[0091] Table 5: Room Temperature Mechanical Properties Test Data of Copper Foil Between Continuous Production Batches
[0092] According to Table 5 and Figure 5 and Figure 6 The stability of the macroscopic mechanical properties of copper foil under continuous production directly reflects the control level of the microscopic electrocrystallization environment. In Example 1, the tensile strength remained stable in the range of 310.8 to 317.9 MPa within 24 hours, and the elongation deviation was strictly controlled within 0.4%. This was due to the dead zone locking and trend prediction of the closed-loop algorithm, which curbed the drastic fluctuations in the additive concentration. At the same time, the polymer leveling agent maintained a constant polarization barrier. In Comparative Example 1, the electrolyte concentration fluctuated periodically due to the lag in manual detection, which caused disordered switching of the grain growth state and a significant divergence in tensile strength. In Comparative Example 4, traditional gelatin degraded rapidly under high current. After losing stable polarization constraints, the microscopic grains were stacked in coarse columnar shapes, and the overall mechanical properties of the material were low and fluctuated greatly. This shows that the deep integration of strongly adsorbed polymer materials with anti-vibration control algorithms is the key to anchoring macroscopic mechanical properties.
[0093] Test Example 6: Example 1 and Example 2, which are equipped with a complete closed-loop control system, were selected as parallel test objects. Example 2, which uses a dead zone and trend prediction algorithm, and Example 1, which relies on traditional manual offline detection and drug adjustment, were removed. The copper foil width of each production line was uniformly set to 1.3 meters, the winding speed was locked at 6 m / min, and the target roughness Ra qualified range was set to 0.3 μm to 0.5 μm. The system was started and maintained in normal operation.
[0094] When each system group has been running continuously for 30 minutes, the test personnel, without informing the central control system, instantly poured 500 ml of 99% pure sodium 3-mercapto-1-propanesulfonate concentrate into the main electrolytic cell. This operation is intended to simulate an unexpected situation in an industrial setting where the liquid supply valve leaks or is misconfigured, forcibly breaking the original cathode polarization balance and inducing a precipitous drop in product roughness.
[0095] Record the exact time point of the injection of the disturbance fluid; for Example 1, Example 2 and Comparative Example 2, the PLC system is completely entrusted to autonomous identification and reverse flow control based on online lidar data; for Comparative Example 1, in accordance with the current management system of the workshop, manual routine sample cutting is performed 45 minutes after the disturbance occurs. After 15 minutes of offline laboratory testing confirms that the Ra value exceeds the standard, the operator manually cuts off the supply of accelerator and significantly increases the speed of the leveling agent pump based on experience.
[0096] Through data acquisition terminals and the production management MES system, the total time elapsed for each group from the moment the Ra value fell below the lower limit of 0.3μm until it stably returned to the acceptable range of 0.3μm to 0.5μm for 5 consecutive minutes; combined with a constant conveyor speed of 6m / min and a gate width of 1.3 meters, the physical length of the associated waste products and the total scrap area caused by this disturbance event were calculated.
[0097] Table 6: Statistics on Recovery Response and Defective Product Output of Various Systems under Sudden Disturbance
[0098] According to Table 6 and Figure 7 Different control logics exhibited significant differences in recovery efficiency when dealing with sudden concentration disturbances. Comparative Example 1 relied on manual offline management, resulting in a long detection blind zone. The delayed and drastic manual intervention led to a total duration of roughness exceeding the limit of 138.5 minutes and a defective area of 1080.30 square meters. Although Comparative Example 2 could quickly identify online, the lack of an adjustment dead zone caused repeated and drastic fluctuations in the concentration of leveling agent in the tank due to high-frequency control, leading to grain distortion and stacking, and extending the recovery time to 92.4 minutes. Example 1 quickly captured the anomaly through a radar system and used the quantitative pump compensation action and forced setting of the adjustment dead zone to reserve sufficient convection time for the diffusion of the leveling agent. When the new inhibition film was gradually established, the trend feedforward logic promptly cut off the supply of excess liquid, achieving a flexible and stable pull-up and compressing the total duration of the system exceeding the limit to within 28.7 minutes, minimizing the output of defective products.
[0099] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A production process for maintaining stable copper foil properties through online roughness detection, characterized in that, Includes the following steps: S1, prepare the basic electrolyte, and combine sulfur-containing compounds, polyether compounds, and quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymers into a mixed additive mother liquor; inject the mixed additive mother liquor into the electrolytic cell through a metering pump, so as to control the cathode deposition potential by utilizing the dual mechanism of steric hindrance and charge repulsion of the crosslinked copolymer. S2, a detection point is set between the electrolytic cell outlet and the winding machine to collect the roughness data of the copper foil surface in real time; S3, the data acquisition and processing module extracts the values in the data window according to the set period, removes abnormal extreme values based on the 3σ criterion, calculates the arithmetic mean of the remaining effective values, and compares it with the preset target roughness range. S4, when the arithmetic mean deviates from the target range, the data acquisition and processing module sends a flow adjustment command to the metering pump; after the command is executed, the system is forced to enter a period of adjustment lock-in, during which only data is collected and any new flow adjustment command is blocked to compensate for the pure lag time of the additive fluid being transferred to the cathode roller surface; S5. After the lockout period ends, the system calculates the slope of the change in the average roughness. If the average value still exceeds the limit, based on the comparison between the absolute value of the change slope and the preset slope threshold, the system selects to multiply the subsequent adjustment amount by the weight coefficient for de-rating adjustment or to perform full step adjustment, and re-enters the adjustment lockout period. If the average value returns to the target range, the current flow rate remains unchanged.
2. The production process according to claim 1, characterized in that, In step S1, the specific parameters of the basic electrolyte are configured such that the basic electrolyte contains 70-100 g / L of copper ions, 90-130 g / L of sulfuric acid, and 20-45 mg / L of chloride ions; at the same time, a heat exchange circulation loop is configured to control the electrolyte temperature to be stable at 45-60℃, so as to ensure the mass transfer rate of copper ions and the deposition morphology during the electrolysis process.
3. The production process according to claim 1, characterized in that, In step S1, the mixed additive mother liquor needs to be continuously injected through a metering pump to maintain the concentration of sulfur-containing compounds in the electrolytic cell solution at 1.0-5.0 mg / L, the concentration of polyether compounds at 5.0-20.0 mg / L, and the concentration of quaternized polyvinyl imidazole-epoxychloropropane crosslinked copolymer at 0.5-3.0 mg / L; wherein, the sulfur-containing compounds are specifically selected from sodium polydisulfide dipropanesulfonate or sodium 3-mercapto-1-propanesulfonate, and the polyether compounds are specifically polyethylene glycol.
4. The production process according to claim 1, characterized in that, In step S1, before starting the automatic closed-loop control system, the production line needs to be initialized: the conveyor speed of the copper foil production line is set to be constant at 6m / min, and based on the volume of the electrolytic cell and the state of the base liquid, the initial flow rate of the metering pump is set to 3.0-8.0L / min, so as to establish and maintain the basic cathode polarization potential in the early stage of electrolysis.
5. The production process according to claim 1, characterized in that, In step S2, the hardware setup and operation mode for real-time acquisition are as follows: In the constant speed belt travel area between the electrolytic cell outlet and the winding machine, 13 detection points are uniformly set along the width direction of the copper foil using a non-contact laser roughness meter; and the signals of each detection point are synchronously acquired at a sampling frequency of 1Hz-5Hz to form a real-time roughness dataset covering the entire width of the copper foil.
6. The production process according to claim 1, characterized in that, In step S3, the specific data processing mechanism for data filtering and analysis is as follows: the data acquisition and processing module extracts the dataset collected within each 10-second time window as a data extraction window; after removing outliers that deviate from the arithmetic mean by more than 3 times the standard deviation, the arithmetic mean of the valid data within the data window is recalculated; and the result is compared with the preset target roughness range of 0.3μm to 0.5μm for limit judgment.
7. The production process according to claim 1, characterized in that, In step S4, the data acquisition and processing module generates corresponding flow increase or decrease adjustment commands based on the deviation direction. The specific flow adjustment ratio is set as follows: for every 0.1 μm that the arithmetic mean exceeds or falls below the target range, the data acquisition and processing module controls the flow rate of the metering pump to decrease or increase by 0.1-0.5 L / min.
8. The production process according to claim 1, characterized in that, In step S4, the duration of the adjustment lockout period that the system is forced to enter after the instruction is executed is set to 3 to 10 minutes. During the adjustment lockout period, the data acquisition and processing module continues to execute steps S2 and S3 to maintain continuous monitoring of the trend of copper foil roughness change, but actively intercepts and blocks any new flow adjustment instructions generated based on the latest arithmetic average value until the countdown of the current lockout period ends.
9. The production process according to claim 1, characterized in that, In step S5, the specific data extraction and comparison method for calculating the slope of change is as follows: At the end of the current adjustment lock period, the system extracts the roughness arithmetic mean within the latest 1-minute time window, and calculates the difference between the extracted roughness arithmetic mean and the value recorded at the beginning of the current adjustment lock period to obtain the slope of change representing the roughness recovery trend; the system presets the absolute value threshold of the slope to be 0.05-0.08μm / min.
10. The production process according to claim 9, characterized in that, In step S5, the specific rules for executing the adjustment logic based on trend prediction are as follows: if the absolute value of the change slope is greater than or equal to the preset slope threshold, it indicates that the roughness is under control and rapidly approaching the target range, then the theoretical adjustment amount calculated according to claim 7 is multiplied by a weighting coefficient of 0.3-0.7 for de-rating adjustment; if the absolute value of the change slope is less than the preset slope threshold, it indicates that there is a serious lag in roughness recovery, then full-step adjustment without discount is executed; after the above single adjustment action is completed, the system immediately re-triggers a new round of adjustment lock-in period.